2003
DOI: 10.1093/ageing/32.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a cut-off point for normal mobility: a comparison of the timed 'up and go' test in community-dwelling and institutionalised elderly women

Abstract: residential and mobility status were identified as the strongest predictors of timed up and go test performance. We recommend the timed up and go test as a screening tool to determine whether an in-depth mobility assessment and early intervention, such as prescription of a walking aid, home visit or physiotherapy, is necessary. Community-dwelling elderly women between 65 and 85 years of age should be able to perform the timed up and go test in 12 seconds or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
382
4
48

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 634 publications
(469 citation statements)
references
References 13 publications
16
382
4
48
Order By: Relevance
“…A greater proportion of participants with type 2 DM had a diagnosis of osteoarthritis of at least 1 joint (16 out of 30 [53.3%] versus 5 out of 30 [16.7%]; P ϭ 0.008) (data not shown). Women with type 2 DM had a higher mean BMI (P Ͻ 0.001) and fewer of these participants completed the TUG test in under 12 seconds, a normal cutoff point for community-dwelling adults (P ϭ 0.011) (28). The serum biochemistry and antihyperglycemic medications used for participants with type 2 DM are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater proportion of participants with type 2 DM had a diagnosis of osteoarthritis of at least 1 joint (16 out of 30 [53.3%] versus 5 out of 30 [16.7%]; P ϭ 0.008) (data not shown). Women with type 2 DM had a higher mean BMI (P Ͻ 0.001) and fewer of these participants completed the TUG test in under 12 seconds, a normal cutoff point for community-dwelling adults (P ϭ 0.011) (28). The serum biochemistry and antihyperglycemic medications used for participants with type 2 DM are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…A timed up-and-go (TUG) test was used to assess the participant's physical mobility. A normative cutoff point of 12.0 seconds was used for TUG test performance (28).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…In contrast an increase in other angular velocity measures was associated with a reduced likelihood of declining balance. This finding was anticipated as it is reported that a shorter TUG time is associated with more positive health outcomes [9,10]. The current study also investigated the relationship between variance and the change in variance over time for gait parameters, and change in balance over time.…”
Section: Discussionmentioning
confidence: 75%
“…The TUG is quick, easy to administer and has been shown to have some predictive power for falls and mobility impairment [9,10]. Additionally, the application of wireless inertial sensors to the lower limbs during the TUG allows measurements such as cadence, stance phase duration and angular velocity to be recorded [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…O TUG apresenta correlação (r = -0.72) com a escala EEB. Bischoff et al 26 consideram para adultos independentes a resolução do teste em até 10 seg. como normal (sem risco de quedas).…”
Section: Participantesunclassified